ATTENTION TO YOUTH ISSUES IN UZBEKISTAN IS ATTENTION TO THE FUTURE OF THE COUNTRY! (International journal of artificial intelligence, 2024)
This article talks about the attention paid to the issue of youth in our country, the work being done to train them in the profession, to reveal their talent in the field of their choice. Also, the information on the attention aimed at helping young people to know their history and forming practical skills for young historians is summarized.